The Relationship Between Research and Environmental Perceptions as a Baseline Study for an Educational Intervention Project - Jimenez, Nydia Nina Valencia; Montes, Jorge Eliecer Ortega; Valencia, Adriana Cecilia Cordero (Journal of Posthumanism, 2025)
This study sought to analyze the relationship between research and the environmental perceptions of ninth grade students with respect to the problems of the Ciénaga Grande del Bajo Sinú wetland (Colombia). The purpose was to diagnose strengths and weaknesses in order to design and implement pertinent educational intervention strategies. A cross-sectional analytical descriptive design was used. The sample was determined by a stratified proportional probability sampling, with a confidence level of 95%, a margin of error of 0.5 and a probability of 0.5, based on a population of 2,909 students enrolled in 14 educational institutions, resulting in a total of 1,000 students. The results showed a trend in which students with lower scores in research also had a low performance in environmental perception, while higher scores had a more limited distribution. It is concluded that it is important to strengthen pedagogical strategies that integrate both areas of knowledge in response to the needs of the context.